SeCl2-Mediated Approach Toward Indole-Containing Polysubstituted Selenophenes - Martins, Guilherme M. (2018)
A novel and efficient SeCl2-mediated chalcogenative cyclization strategy toward 3-selenophen-3-yl-1H-indoles from readily available and conveniently substituted propargyl indoles is described. It entails an unprecedented selenirenium-induced 1,2-indolyl shift prompted by the electrophilic addition of SeCl2 to the triple bond of the propargyl indole, followed by cyclization through the intermediacy of a 1-seleno-1,3-diene. The reaction takes place at room temperature and shows excellent selectivity, broad substrate scope, and wide functional group tolerance.